DEPOSIT-ACCEPTING INSTITUTIONS IN 1996: THE STRUCTURE AND ECONOMIC PERFORMANCE OF THEIR ACTIVITIES - Harchaoui, Tarek M. (Assurances)

(untitled) (HEC Montréal, 1998)
The financial service market place is being dramatically redrawn. Progress in information-processing technology, legislative changes, and market forces have combined to blur the traditional distinctions between deposit-taking institutions (chartered banks, trust companies and credit unions) and other financial institutions. New domestic and foreign competitors are entering the market, some doing so as 'virtual' institutions. Businesses are being reorganized through mergers and acquisitions, joint ventures and niche market positioning to compete with well-capitalized global players. Using an, as yet, untapped dataset, this paper provides an analysis of the activities, market structures and economic performance of deposit-accepting institutions in Canada, in light of the various changes that affected their environment.